Which digital marketing formats work? - Genton, Val-Pierre (Henry Stewart Talks, 2008)
Market opportunity, Buyers are going online to gain knowledge and advertizers are following them, B2B marketing's big challenge: map marketing tactics across buying cycle to maximize MROI, Digital marketing formats, Online display ads, Sponsorship, Search, Email, Web 2.0 social media, Audio/visual, Three simple steps to webcasting, The importance of engagement, Many forms of webcasting, Distribution, Tracking, Measuring ROI
Archived at 2022/03/17